Direct Bisulfite‐Free Detection of 5‐Methylcytosine by Using Electrochemical Measurements Aided by a Monoclonal Antibody. Issue 13 (8th May 2018) - Schiefelbein, Stephan H. H.; Kamal, Ajar; She, Zhe; Rentmeister, Andrea; Kraatz, Heinz‐Bernhard
Abstract: The detection of the epigenetic DNA marker 5‐methylcytosine (5mC) has been the focus of intense research. Here, we report a new detection method, using electrochemical impedance spectroscopy, scanning electrochemical microscopy, and voltammetric measurements on gold electrodes. The direct, label‐free detection of 5mC at different positions within dsDNA is achieved with the aid of a monoclonal anti‐5mC antibody, providing a new tool to monitor nucleic acid modifications. Abstract : Now you see me : Cytosine methylation in DNA plays a key role in epigenetics. Here, a novel antibody‐based, label‐free electrochemical method is reported for the detection of 5‐methylcytosine.